2017
DOI: 10.1073/pnas.1705795114
|View full text |Cite
|
Sign up to set email alerts
|

Systems-guided forward genetic screen reveals a critical role of the replication stress response protein ETAA1 in T cell clonal expansion

Abstract: T-cell immunity requires extremely rapid clonal proliferation of rare, antigen-specific T lymphocytes to form effector cells. Here we identify a critical role for ETAA1 in this process by surveying random germ line mutations in mice using exome sequencing and bioinformatic annotation to prioritize mutations in genes of unknown function with potential effects on the immune system, followed by breeding to homozygosity and testing for immune system phenotypes. Effector CD8 + and CD4 + T-cell formation following i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…6 I) are downregulated during ASFV infection. Previous studies have shown that removing a gene called ETAA1 from mice prevents the animal from producing an immune response to vaccines or infections [ 31 ]. Mice without GPR37 showed delayed phagocytosis of macrophages and a delayed regression of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…6 I) are downregulated during ASFV infection. Previous studies have shown that removing a gene called ETAA1 from mice prevents the animal from producing an immune response to vaccines or infections [ 31 ]. Mice without GPR37 showed delayed phagocytosis of macrophages and a delayed regression of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…For intracellular staining, the eBioscience Foxp3/Transcription factor staining buffer set (ThermoFisher Scientific) and the following antimouse Abs were used: TOX-PE (Clone TXRX10; eBioscience), GzmBallophycocyanin (Clone GB11; ThermoFisher Scientific), and rabbit TCF-1 mAb (Cell Signaling Technology, detected with a secondary anti-rabbit IgG AlexaFluor594 Ab; ThermoFisher Scientific). For peptide restimulation and cytokine staining, splenocytes were incubated with 10 ng/ml LCMV-Cl13 GP 33-41 peptide (Biomolecular Resource Facility, John Curtin School of Medical Research, Australian National University) and Brefeldin (eBioscience) for 5 h at 37˚C as described previously (20); surface stained with Fixable Viability Stain, anti-CD8, and anti-CD45.1 as above; fixed with the BioLegend fixation buffer; and stained intracellularly with TNFa-PE (Clone MP6-XT22; BioLegend), anti-IFN-g-PE-Cy7 (Clone XMG1.2), and IL-2-allophycocyanin (Clone JES6-5H4) (both from eBioscience). Samples were acquired on a BD LSRFortessa X-20 (BD Biosciences) and analyzed using FlowJo software (TreeStar) and GraphPad Prism (GraphPad Software).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Collectively, our data suggest that whereas TopBP1 may be the principal activator of the essential ATR-CHK1 checkpoint pathway, the role of ETAA1 in promoting cell fitness becomes particularly important following impediments to the DNA replication machinery that increase the risk posed by mitotic entry in the presence of unresolved DNA replication intermediates. This could help to explain why ETAA1 deficiency in mice manifests with partially penetrant lethality during embryogenesis and defective clonal expansion of T lymphocytes (Miosge et al, 2017), processes entailing rapid cell proliferation where efficient ETAA1-mediated G2/M checkpoint control may be instrumental in suppressing gross chromosomal instability. Targeted inhibition of ETAA1 functionality might thus unmask a selective vulnerability in highly proliferative malignant cells that generally experience deregulated control of cell cycle progression and elevated replicative stress, providing potential opportunities for the continued evolution of promising therapeutic strategies targeting ATR signaling in cancer (Lecona and Fernandez-Capetillo, 2018).…”
Section: Aad Phosphorylation Is Critical For Etaa1-dependent Suppressmentioning
confidence: 99%
“…Thus, full ATR activation in vertebrate cells relies on independent TopBP1-and ETAA1-mediated pathways, although the precise division of labor in promoting ATRmediated signaling responses remains unclear. For instance, while ablation of TopBP1 or the functionality of its AAD leads to early embryonic lethality in mice, ETAA1 knockout (KO) gives rise to a comparatively mild phenotype characterized by incompletely penetrant embryonic lethality, reduced body size, and defective clonal expansion of T lymphocytes (Zhou et al, 2013;Miosge et al, 2017). Recent studies suggested roles of ETAA1 in promoting an ATR-mediated S/G2 checkpoint suppressing mitotic entry before completion of DNA replication and ATR activation during mitosis, where ATR has been shown to facilitate Aurora B activation at centromeres and accurate chromosome segregation (Kabeche et al, 2018;Saldivar et al, 2018;Bass and Cortez, 2019).…”
Section: Introductionmentioning
confidence: 99%